Strategi Manajemen Sarana dan Prasarana terhadap Pencapaian Akreditasi A di SMP Swasta An-Nizam Medan - Ningsih, Sri Rahayu; Rifai, Muhammad (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
Problems related to facilities and infrastructure management strategies are quite extensive, so it is impossible to resolve them considering the limited time that researchers have. Therefore, it is necessary to limit the problem to further focus this research, namely on the scope facilities and infrastructure management strategy. This research uses a qualitative approach, namely research in order to reveal facts, circumstances, phenomena, variables and circumstances that occur when the research is running and present it according to research in the field. The research used in this research is qualitative with a qualitative descriptive research type because the data collected is in the form of words or images (narrative) so the data is not in the form of numbers. The main activity in every research is data collection. The data collection technique in this research aims to obtain accurate and valid data. In implementing the management strategy for facilities and infrastructure towards achieving accreditation which is expressed in the form of recognition. The accreditation scale is prepared based on the school accreditation guidebook, an activity of assessing the suitability of a school based on criteria that have been determined and carried out by the School Accreditation Body (BAS), the results of which are realized in the form of a ranking. feasibility which includes: a) Curriculum and learning process, b) School administration and management, c) School organization and institutions, d) Facilities and infrastructure, e) Students. f) (school accreditation guidebook).